1995
DOI: 10.1007/bf03401581
|View full text |Cite
|
Sign up to set email alerts
|

The MarR Repressor of the Multiple Antibiotic Resistance (mar) Operon in Escherichia coli: Prototypic Member of a Family of Bacterial Regulatory Proteins Involved in Sensing Phenolic Compounds

Abstract: The MarR family is identified as a group of regulatory factors whose activity is modulated in response to environmental signals in the form of phenolic compounds. Many of these agents are plant derived. Some of the MarR homologs appear more likely to control systems expressed in animal hosts, suggesting that phenolic sensing by bacteria is important in a variety of environments and in the regulation of numerous processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
147
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 45 publications
2
147
0
Order By: Relevance
“…5) analyses also implicated the transcription factor MarR (Ssol_1340) as a member of the mercury regulon. As a regulator of oxidative stress (Alekshun & Levy, 1999;Ariza et al, 1994;Cohen et al, 1993;Ellison & Miller, 2006;Li et al, 2011;Sulavik et al, 1995), its regulated expression may arise from the impact of mercury on free thiols that are titrated by metal sequestration leading to oxidative stress. The MarR transcription factor family shares a common origin in bacteria and archaea as revealed by a conserved N-terminal 40 aa sequence motif (Pérez-Rueda & Collado-Vides, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) analyses also implicated the transcription factor MarR (Ssol_1340) as a member of the mercury regulon. As a regulator of oxidative stress (Alekshun & Levy, 1999;Ariza et al, 1994;Cohen et al, 1993;Ellison & Miller, 2006;Li et al, 2011;Sulavik et al, 1995), its regulated expression may arise from the impact of mercury on free thiols that are titrated by metal sequestration leading to oxidative stress. The MarR transcription factor family shares a common origin in bacteria and archaea as revealed by a conserved N-terminal 40 aa sequence motif (Pérez-Rueda & Collado-Vides, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Structurally homologous MarR proteins are winged helix-turn-helix dimers that bind palindromic promoter sequences to regulate transcription through exogenous ligand binding (Martin & Rosner, 1995). The regulated genes are functionally linked to antibiotic resistance, oxidative stress response, heat shock resistance, virulence, catabolism of aromatic compounds, and export of disinfectants and organic solvents (Alekshun & Levy, 1999;Ariza et al, 1994;Cohen et al, 1993;Ellison & Miller, 2006;Li et al, 2011;Sulavik et al, 1995). Three other MarR proteins of Sulfolobus have now been characterized by crystallography, and their ability to bind DNA is modulated by ligands with various affinities (Kumarevel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These regulators bind DNA through a helix-turn-helix (HTH) motif (Cohen et al, 1993;Sulavik et al, 1995). Members of the MarR family control an assortment of biological functions including the expression of resistance to multiple antibiotics, detergents and oxidative stress agents, organic solvents, and pathogenic factors (Alekshun and Levy, 1999;Miller and Sulavik, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The natural signal for the marRAB operon has not been identified as it remains unknown whether plant-derived napthoquinones are natural inducers (10). It has been shown that the operon is activated by compounds such as salicylate, chloramphenicol, tetracycline, acetaminophen, sodium benzoate, 2,4-dinitrophenol, cinnamate, carbonyl cyanide m-chloro-phenylhydrazone, menadione, and plumbagin (11,12). In the presence of specific antibiotics (such as tetracycline and chloramphenicol; see Refs.…”
mentioning
confidence: 99%